Understanding stigma and coping strategies among HIV-negative Muslim wives in serodiscordant relationships in a Javanese community, Indonesia - Agnes, Yeni Lufiana Novita; Songwathana, Praneed (Belitung Raya Foundation, Indonesia, 2021)
Background: Although advanced treatment and accessibility of HIV/AIDS prevention and care have been increased, HIV-related stigma persists in the Indonesian community, especially among HIV-negative Muslim wives in a serodiscordant relationship. Therefore, understanding their coping strategies of the stigma is a necessity. Objective: The study aimed to explore HIV-related stigma and coping strategies of HIV-negative Muslim wives in a serodiscordant relationship. Methods: A qualitative study was conducted among seven HIV-negative Muslim wives in a serodiscordant relationship who experienced stigma. Data were collected by in-depth interview, and content analysis was used for data analysis. Findings: Three themes emerged from the data. The first theme was the meaning of HIV/AIDS to Muslim wives, including perceiving HIV as a wanita nakal (immoral women) disease, perceiving HIV causes death, assuming herself as a carrier, and presuming HIV is less harmful than Diabetes Mellitus. The second theme was HIV-related stigma experiences, including being shunned by people, rejected by a midwife, and humiliated by a health worker. Finally, the third theme was coping strategies with the stigma, consisting of hiding the husband's HIV-positive status from the neighbors, disclosing HIV-positive status to a selective person, seeking support from the peer group, and strengthening the relationship among family members. Conclusion: HIV/AIDS-related stigma affected people living with HIV/AIDS and their families, and it becomes a barrier to HIV/AIDS reduction programs in the marriage relationship. These findings will be beneficial to nurses and other health professionals to develop stigma reduction interventions related to HIV/AIDS.